Miscibility Development Computation in Enhanced Oil Recovery by Flare Gas Flooding - Samadhi, Tjokorde Walmiki; Siagian, Utjok W.R.; Budiono, Angga P. (ITB Journal Publisher, LPPM ITB, 2012)
The use of flare gas as injection gas in miscible gas flooding enhanced oil recovery (MGF-EOR) presents a potential synergy between oil production improvement and greenhouse gases emission mitigation. This work is a preliminary evaluation of the feasibility of miscible flare gas injection based on phase behavior computations of a model oil (43% n-C5H12 : 57% n-C16H34) and a model flare gas (91% CH4 : 9% C2H6). The computations employed the multiple mixing-cell model with Peng-Robinson and PC-SAFT equations of state, and compared the minimum miscibility pressure (MMP) value in the cases of flare gas injection and CO2 injection. For CO2 injection, both equations of state produced MMP values close to the measured value of 10.55 MPa. Flare gas injection MMP values were predicted to be 3.6-4.5 times those of CO2 injection. This very high MMP implies high gas compression costs, and may compromise the integrity of the reservoir. Subsequent studies shall explore the gas -oil miscibility behavior of mixtures of flare gas with intermediate hydrocarbon gases and CO2, in order to identify a suitable approach for rendering flare gas feasible as an injection gas in MGF-EOR.